Ten little fingers and ten little toes - Fox, Mem, 1946-; Oxenbury, Helen (Orlando [Fla.] : Harcourt, 2008)
Rhyming text compares babies born in different places and in different circumstances, but they all share the commonality of ten little fingers and ten little toes.
Keywords: Stories in rhyme; Babies -- Fiction; Fingers -- Fiction; Toes -- Fiction; Infants -- Juvenile fiction; Fingers -- Juvenile fiction; Toes -- Juvenile fiction